THE INFLUENCE OF RELIGIOSITY, CULTURAL BE-LIEFS AND MARGIN LEVELS ON CUSTOMER DECI-SIONS IN USING ISLAMIC BANK FINANCING PROD-UCTS IN TANAH DATAR REGENCY - Cantika, Abdi Dea; Asyari, Asyari (Inovbiz: Jurnal Inovasi Bisnis, 2023)
This research is motivated by the low growth rate of microfinance in Islamic banks in the Tanah Datar Regency area. This is evidenced by data published by OJK from 2019 to 2022 and reinforced by BSI's internal data in the first quarter to the third quarter of 2022 which confirms that the lowest microfinance growth is located in Tanah Datar Regency / Batusangkar. This is interesting to examine further because as Tanah Datar Regency, which has a majority Muslim population and the forerunner of the establishment of Minangkabau, which has a very strong historical, religious and cultural background, there should be no element of rejection that occurs in the community to switch to using financing products in Islamic banks.The quantitative method was used in this study using a sample of 143 MSME players who have not used Islamic bank financing products in Tanah Datar Regency. The data were collected using a questionnaire and analyzed using statistical software, namely smart-PLS 3.0 to see the effect of religiosity, cultural beliefs and margin levels on the decisions of MSME players in using Islamic bank financing products in Tanah Datar Regency. The results of the study prove that the decision of MSME players in Tanah Datar Regency to use financing products in Islamic banks is influenced by the variables of religiosity, cultural belief and margin level positively and significantly. This shows that religiosity, cultural belief and margin rates are crucial points for Islamic banks that will influence the community of MSME players to switch to using Islamic banking. Furthermore, this study offers a strategy to increase the market share of Islamic banks, namely through approaches to traditional and religious leaders who are influential in the community environment of Tanah Datar Regency and increasing the religious understanding of MSME players in Tanah Datar Regency and reconsidering the determination of the margin rate for channeling financing to the community, especially MSME players.